Bio-Waste Products of Mangifera indica L. Reduce Adipogenesis and Exert Antioxidant Effects on 3T3-L1 Cells - Giovanni Pratelli; Daniela Carlisi; Antonella D'Anneo; Antonella Maggio; Sonia Emanuele; Antonio Palumbo Piccionello; Michela Giuliano; Anna De Blasio; Giuseppe Calvaruso; Marianna Lauricella (MDPI AG, 2022)
Several studies highlighted the beneficial value of natural compounds in the prevention and treatment of obesity. Here, we investigated the anti-obesity effects of extracts of peel and seed of mango (Mangifera indica L.) cultivated in Sicily (Italy) in 3T3-L1 cells. Mango Peel (MPE) and Mango Seed (MSE) extracts at a 100 µg/mL concentration significantly reduced lipid accumulation and triacylglycerol contents during 3T3-L1 adipocyte differentiation without toxicity. HPLC-ESI-MS analysis showed that both the extracts contain some polyphenolic compounds that can account for the observed biological effects. The anti-adipogenic effect of MPE and MSE was the result of down-regulation of the key adipogenic transcription factor PPARγ and its downstream targets FABP4/aP2, GLUT4 and Adipsin, as well SREBP-1c, a transcription factor which promotes lipogenesis. In addition, both MPE and MSE significantly activated AMPK with the consequent inhibition of Acetyl-CoA-carboxylase (ACC) and up-regulated PPARα. The addition of compound C, a specific AMPK inhibitor, reduced the effects of MPE and MSE on AMPK and ACC phosphorylation, suggesting a role of AMPK in mediating MPE and MSE anti-lipogenic effects. Notably, MPE and MSE possess an elevated radical scavenging activity, as demonstrated by DPPH radical scavenging assay, and reduced ROS content produced during adipocyte differentiation. This last effect could be a consequence of the increase in the antioxidant factors Nrf2, MnSOD and HO-1. In conclusion, MPE and MSE possesses both anti-adipogenic and antioxidant potential, thus suggesting that the bio-waste products of mango are promising anti-obesity natural compounds.